1999
DOI: 10.1063/1.1149324
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy in the extreme ultraviolet on an electron beam ion trap

Abstract: Articles you may be interested inExtended-range grazing-incidence spectrometer for high-resolution extreme ultraviolet measurements on an electron beam ion trapa) Rev. Sci. Instrum. 85, 11E422 (2014);Highly charged metal ions produced from volatile organometallic compounds in a room temperature electron beam ion trap Rev.High energy operation of the Tokyo-electron beam ion trap/present status Rev. Sci. Instrum. 71, 687 (2000)A compact grazing-incidence spectrometer was implemented on the Livermore electron bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 21 publications
0
42
0
Order By: Relevance
“…For the present measurement, we used a medium-resolution flat-field grating spectrograph (FFS; Beiersdorfer et al 1999b). The instrument was equipped with a 1200 /mm R = 5 m grating and operated at an angle of incidence of 87…”
Section: Measurementmentioning
confidence: 99%
“…For the present measurement, we used a medium-resolution flat-field grating spectrograph (FFS; Beiersdorfer et al 1999b). The instrument was equipped with a 1200 /mm R = 5 m grating and operated at an angle of incidence of 87…”
Section: Measurementmentioning
confidence: 99%
“…The spectra were studied using a moderate-resolution broad-band grating spectrometer of the same type used for grazing-incidence measurements at the SSPX, NSTX, LTX and Alcator C-Mod magnetic fusion facilities [42][43][44][45][46][47]. The instrument employs a 1200-line/mm flat-field grating with a radius of curvature of 5.6 m. The diffracted rays are focused on a Princeton Instruments back-illuminated CCD camera with a 1024 × 1340 array of pixels, each of a size of 20 µm × 20 µm.…”
Section: Survey Measurementsmentioning
confidence: 99%
“…The higher energy is sufficient to produce charge states as high as Fe xvi. The spectra were recorded with the grazing-incidence spectrometer described by Beiersdorfer et al [13], which employs a 1200 line/mm flat-field grating developed by Harada & Kita [14] with a 3 o angle of incidence. Readouts were taken with a back-illuminated, liquid nitrogen-cooled CCD camera with a one inch square array of 1024 × 1024 pixels.…”
Section: Spectroscopic Measurementsmentioning
confidence: 99%
“…A foil comprised of a 2000Å thick aluminum layer on top of 1000Å of paralene was placed in front of the grating in order to screen out emission from lines with wavelengths below 170Å. The wavelength scale was established using the well known K-shell emission lines of nitrogen, in particular the N vii Lyman-α line and the N vi resonance line commonly referred to as w, as described by Beiersdorfer et al [13], observed in higher (7th through 10th) orders. The wavelengths of the iron emission lines in this wavelength region are well known, and we have not attempted to improve upon those data.…”
Section: Spectroscopic Measurementsmentioning
confidence: 99%